ACCOMMODATING WORLD ENGLISHES IN DEVELOPING EFL LEARNERSâ ORAL COMMUNICATION - Nur Mukminatien (TEFLIN Journal: A publication on the teaching and learning of English, 2012)
This article aims to discuss issues of World Englishes (WEs) and the implications in ELT. It explores the extent to which WEs are taken into account as emerging English varieties different from inner circle varieties, how WEs should be accomodated by English teachers, and which standard to adopt to accommodate learnerâs linguistic needs for international communication. It would help ELT practitioners adjust their current practices through the inclusion of varieties of WEs in developing learnersâ oral communication. This offers relevant pedagogical movement to argue that changes should be made about the way English is valued and taught.